EFFECT OF SELF-EFFICACY ON WORK ENGAGEMENT MEDIATED BY HRD CLIMATE ON OUTSOURCED BANK EMPLOYEES - Sandroto, Christine Winstinindah; Wijaya, Veranica (Review of Management and Entrepreneurship, 2020)
Human resources play a vital role in every company because human resources are the cogs for the running of the company. Nowadays, competition in any company is getting tougher, including the banking industry. This study aims to prove the effect of Self-efficacy on Work Engagement mediated by HRD Climate. This research was conducted at PT X as a third party, which is an outsourcing company for bank employees in Jakarta. Questionnaires were distributed to 150 employees, and data processing was done using SPSS v22 software and Hayes PROCESS v3 macros. The results of this study indicate that there is a positive and significant influence between the variable Self-efficacy on Work Engagement mediated by HRD Climate, with a more significant direct effect between the Self-efficacy variable on Work Engagement on outsourced bank employees in Jakarta.